Empirical classifications of types among delinquent referrals to a child guidance clinic - Hart, I; McQuaid, P (Economic & Social Studies, 1974)
A major difficulty in formulating treatment programmes for juvenile offenders is the multiplicity of causes and circumstances of anti-social behaviour. This study uses factor and cluster analysis to search for syndromes of cause and circumstance among 107 young people referred to a Dublin child guidance clinic for anti-social behaviour. Results are compared with those for 150 Dublin boys on probation who were tested by Hart at about the same time.
Keywords: Child Guidance